PENGARUH PELAYANAN PRIMA TERHADAP LOYALITAS PELANGGAN PADA PT FAST FOOD INDONESIA TBK KFC CABANG RAMAYANA CIBUBUR JAKARTA TIMUR bilgah 1) bilgah.bgh@bsi.ac.id Unversitas BSI fakultasTeknik Informasi - Bilgah Bilgah (Universitas Bina Sarana Informatika, 2019)
Abstract - The best service the company provides to customers can create customer satisfaction. In this research, the method used is a quantitative method and using software SPSS 22.0. The data used are observation, interview, questionnaire, and literature study. The number of samples as many as 100 respondents on KFC customers RAMAYANA CIBUBUR Branch. The result of the correlation calculation of 0.771 means a strong relationship between excellent service to customer loyalty. In determination coefficient test is known that the value of R Square is 59.3% and the remaining 40.7% influenced by other factors that affect customer satisfaction such as suitability, endurance, and ease. And then the result regression analysis obtained Y = 14.447 + 0.926X which indicates that if the excellent service is considered constant, then customer loyalty will be positive and significant. Keywords: Excellent Service, customer loyalty